PENGARUH PENGUASAAN VEKTOR TERHADAP HASIL BELAJAR FISIKA MATERI POKOK GAYA DI KELAS XI SMA NEGERI 1 SIPIROK - Seri Asmaidah (JURNAL PhysEdu (PHYSICS EDUCATION), 2023)
The aim of this research was to describe whether there was any significant influence of vector mastery and physic achievement in force subject at the eleventh grade students of SMA Negeri1Sipirok. The method of this research was descriptive and coorrelational. By using random sampling technique, the writer took 39 students from 120 students. Test was used to collect the data. Based on descriptive analysis, average of vector mastery was 67.5, it was categorized “enough” and the average of force subject was 76.1, it was categorized “good”. Based statistic inferential analysis by using r produc moment and ttest formula to test hypothesis, it could be gotten rcount = 0.609 and rtable = 0.316 at error level 5%. It could be seen rcount was greater than rtable (0.609>0.316). This score was compared with ttest formula,it could be gotten tcount = 4.668 and ttable = 1.686 at error level 5%. It could be seen tcount was greater than ttable (4.668 >1.686). It means alternative hypothesis was accepted. In the other words, there was any significant influence of vector mastery and physic achievement in force subject at the eleventh grade students of SMA Negeri1 Sipirok.